2019
DOI: 10.1016/j.rmed.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Prescriptive adherence to GINA guidelines and asthma control: An Italian cross sectional study in general practice

Abstract: Background: Although general practitioners (GPs) are frequently the first healthcare professionals whom asthma patients refer to for their symptoms, few studies have explored the extent of adherence to guidelines for asthma management based on data provided directly by GPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
(27 reference statements)
1
25
0
Order By: Relevance
“…Further, in all treatment steps, subjects with uncontrolled asthma reported more asthma exacerbations, healthcare utilization, and worse physical health than those with controlled asthma. From a healthcare perspective, nonadherence to asthma guidelines is common and may cause an uncontrolled disease (21)(22)(23). Guidelines recommend the use of validated questionnaires to identify the level of asthma control (1,11), nevertheless only a minority of physicians use these questionnaires on a regular basis (21,24).…”
Section: Discussionmentioning
confidence: 99%
“…Further, in all treatment steps, subjects with uncontrolled asthma reported more asthma exacerbations, healthcare utilization, and worse physical health than those with controlled asthma. From a healthcare perspective, nonadherence to asthma guidelines is common and may cause an uncontrolled disease (21)(22)(23). Guidelines recommend the use of validated questionnaires to identify the level of asthma control (1,11), nevertheless only a minority of physicians use these questionnaires on a regular basis (21,24).…”
Section: Discussionmentioning
confidence: 99%
“…One study aimed to evaluate adherence to GINA guidelines and its relationship with disease control in real life. According to GINA guideline asthma classification, the results indicated overtreatment of intermittent and mild persistent asthma, as well as a general poor adherence to GINA treatment recommendations, despite its confirmed role in achieving a good asthma control 15 . In the US, nationally representative data showed that agreement with and adherence to asthma guidelines was higher for specialists than for primary care clinicians, but was low in both groups for several key recommendations 16 .…”
Section: Guidelinesmentioning
confidence: 99%
“…Individuals' with uncontrolled asthma have increased risk of morbidity and mortality, diminished quality of life, and elevated symptom burden, and ways to improve clinical care and asthma outcomes are needed (3). Fundamental to this objective is promoting multi-level adherence to evidence-based guidelines (4). It is commonly acknowledged that patients ignore symptoms, take medications inconsistently, and have poor self-management (5,6).…”
Section: Introductionmentioning
confidence: 99%